2016
DOI: 10.1007/s00125-016-4058-5
|View full text |Cite
|
Sign up to set email alerts
|

Survival or death: a dual role for autophagy in stress-induced pericyte loss in diabetic retinopathy

Abstract: Aims/hypothesisIntra-retinal extravasation and modification of LDL have been implicated in diabetic retinopathy: autophagy may mediate these effects.MethodsImmunohistochemistry was used to detect autophagy marker LC3B in human and murine diabetic and non-diabetic retinas. Cultured human retinal capillary pericytes (HRCPs) were treated with in vitro-modified heavily-oxidised glycated LDL (HOG-LDL) vs native LDL (N-LDL) with or without autophagy modulators: green fluorescent protein–LC3 transfection; small inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
94
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(98 citation statements)
references
References 45 publications
2
94
0
2
Order By: Relevance
“…Research showed a substantial increase in autophagic activity in retinal ganglion cells in mice with streptozotocin-induced diabetes, which indicates that cell death develops with the initial dysregulation of autophagy before the appearance of signs of vascular damage and without a strong involvement of apoptosis [27] . Further research revealed that autophagy has a dual role in DR: under mild stress, it is protective for human retinal capillary pericytes, while under more severe stress it promotes cell death [28] . Thus, the concrete mechanisms of autophagy in DR require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Research showed a substantial increase in autophagic activity in retinal ganglion cells in mice with streptozotocin-induced diabetes, which indicates that cell death develops with the initial dysregulation of autophagy before the appearance of signs of vascular damage and without a strong involvement of apoptosis [27] . Further research revealed that autophagy has a dual role in DR: under mild stress, it is protective for human retinal capillary pericytes, while under more severe stress it promotes cell death [28] . Thus, the concrete mechanisms of autophagy in DR require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…These UPR branches coordinate the regulation of protein translation and transcription programs to restore ER homeostasis [35]. Unresolved ER stress activates proapoptotic and proinflammatory genes, such as those encoding CHOP, which contributes to retinal inflammation and vascular dysfunction in ischemic retinopathy and DR [36]. In endothelial cells, activation of the UPR plays a critical role in regulating cell proliferation, apoptosis and angiogenesis [37], and in this pathway, CHOP is a well-characterized marker for the cell transition from ER stress to apoptosis [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the retina is susceptible to ROS because of high-energy demands and exposure to light (Nita & Grzybowski, 2016 Kowluru, 2008). Therefore, oxidative stress can play an essential role in retinal capillary apoptosis (Fu et al, 2016;Kowluru, 2005).…”
Section: Oxidative Stress and Diabetic Retinopathymentioning
confidence: 99%